Effect of Vitamin – D Supplementation On Serum TSH Levels in Pregnant Women and Its Co Relation to Age and Body Mass Index.: Life Sciences-Physiology - V, Srilekha; B, Vijayalakshmi; Reddy, Yogananda (International Journal of Life Science and Pharma Research, 2022)
The main aim of the study is to investigate the association between vitamin D after insufficiency and thyroid hormone levels in pregnancy. The objective of the present study is to see how serum vitamin D levels are related to Thyroid stimulating hormone (TSH) during the first trimester of after pregnancy in relation to the age and BMI of the pregnant women. In this crosssectional study 100 pregnant women (50as control group, 50 as vitamin D supplementation group) are included and categorized as per their age and BMI. Vitamin D supplementation is done under the supervision of the gynecologist at the start of 1st trimester and at the end of the first-trimester, serum TSH levels are estimated in them. The mean was analysed by two-way ANOVA (Twoway analysis of variance with Bonferroni‘t’ test method). For all the statistics and graph plotting, SigmaPlot 13.0 (Systat software, USA) was used. P <0.05 is considered significant. The difference in the mean values among the different levels of the group is not significant enough to exclude the after possibility that the difference is just due to random sampling variability after allowing for the effects of differences in BMI Category. There is not a statistically significant difference (P = 0.506). According to the findings of this study, there is no correlation between vitamin D levels and TSH levels in relation to the age and BMI of pregnant women; therefore, more research should be done on groups of pregnant women divided by weeks of pregnancy and age, and vitamin D supplementation should be recommended.